CMV-Positive Biliary Atresia in Infants: A Review of Prognosis and Therapeutic Impact - Rahmadiena, Qonita; Rahmah, Nailah; Karyanti, Mulya Rahma; Rahman, Himawan Aulia (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Biliary atresia (BA) is a progressive cholangiopathy of infancy that can lead to end-stage liver disease and is the leading indication for pediatric liver transplantation. Among various proposed etiologies, cytomegalovirus (CMV) infection has emerged as a significant factor, giving rise to a distinct clinical subset known as CMV-positive BA. Discussion: CMV-positive BA is frequently associated with delayed diagnosis, increased incidence of postoperative cholangitis, and advanced liver fibrosis at initial presentation. These features contribute to lower rates of jaundice clearance and native liver survival. Mortality is also higher in CMV-positive patients than in their CMV-negative. Diagnostic methods include performing polymerase chain reaction (PCR) tests on saliva, urine, or dried blood spot samples, as well as conducting abdominal ultrasound examinations that focus on identifying specific indicators, such as the triangular cord sign, which is commonly observed in patients with BA. Antiviral therapy, particularly with ganciclovir or valganciclovir, shows promise in improving native liver outcomes in CMV-positive BA patients. Early surgical intervention remains critical, yet CMV-positive BA often presents later, worsening prognosis. Preventive strategies are under investigation, including maternal CMV screening and neonatal testing. Conclusion: Early identification and tailored antiviral intervention may play a critical role in altering the disease trajectory. Increased awareness of CMV-positive BA is essential for timely diagnosis and optimal management. This review emphasizes the need to recognize CMV-positive BA as a clinically important biliary atresia subset with distinct pathophysiology and worse prognosis, underscoring the importance of early CMV screening and targeted antiviral therapy.